The galloyl moiety enhances the inhibitory activity of catechins and theaflavins against α-glucosidase by increasing the polyphenol–enzyme binding interactions. Issue 1 (9th December 2020) - Sun, Lijun; Song, Yi; Chen, Yujie; Ma, Yilan; Fu, Minghai; Liu, Xuebo
Abstract : Galloyl moiety plays an important role in binding of catechins and theaflavins with α-glucosidase. Abstract : The inhibition properties of 10 tea polyphenols against α-glucosidase were studied through inhibition assay, inhibition kinetics, fluorescence quenching and molecular docking. It was found that the inhibitory activity of polyphenols with a 3 and/or 3′ galloyl moiety (GM) was much higher than that without a GM. The GM could enter into the active site of α-glucosidase and bind with the catalytic amino acid residues through hydrogen bonding and π-conjugation, thus playing an important role in the competitive inhibition of catechins and theaflavins. The positive linear correlations among the constants characterizing the inhibitory activity and binding affinity of tea polyphenols to α-glucosidase indicate that enzyme inhibition by polyphenols is caused by the binding interactions between them, and that the combination of the characterization methods for polyphenol–glucosidase binding is reasonable. In addition, the in vivo hypoglycemic effects of galloylated polyphenols suggest that the GM may be considered as a pharmaceutical fragment for the alleviation of type II diabetes symptoms through α-glucosidase inhibition.